Interpretations of a non - bindind "Supreme Interpreter"? Reflections on the role of Peruvian Constitutional court, a purpose of an amendment to its legal recent regulation - López Flores, Luciano (2016)
This paper builds on the amendment ofArticle 10 of the Normative of the Peruvian Constitutional Court to analyze a problem: the distinctions between the types of decisions handed down by the Constitutional Court (binding precedent, constitutional jurisprudence, interpretative rulings). It is held that this distinction undermines the status and role of Supreme Interpreter of the Constitution which currently holds the Constitutional Court. And it is argued that the type of decisions is inconsistent with that role.